2017
DOI: 10.1371/journal.pone.0171322
|View full text |Cite
|
Sign up to set email alerts
|

Ascofuranone inhibits lipopolysaccharide–induced inflammatory response via NF-kappaB and AP-1, p-ERK, TNF-α, IL-6 and IL-1β in RAW 264.7 macrophages

Abstract: The natural fungal compound ascofuranone (5-chloro-3-[(2E,6E)-7-[(2S)-5,5-dimethyl-4-oxo-tetrahydrofuran-2-yl]-3-methyl-octa-2,6-dienyl]-2,4-dihydroxy-6-methyl-benzaldehyde, MW 420.93) (AF) isolated from Ascochyta viciae has been known to promote cell cycle arrest and inhibit invasion of tumor cells. We have previously studied a structurally similar compound ascochlorin (ASC; MW 404.93) with regard to its anti-inflammatory activity in LPS- stimulated RAW 264.7 macrophages. In order to examine the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 31 publications
0
36
1
Order By: Relevance
“…Previous studies have revealed that NF‐κB signaling pathway is one of the most important pathways that are activated in macrophages under the pathogen challenge . Thus, we aimed to study whether the anti‐inflammatory ability of curcumin is associated with NF‐κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that NF‐κB signaling pathway is one of the most important pathways that are activated in macrophages under the pathogen challenge . Thus, we aimed to study whether the anti‐inflammatory ability of curcumin is associated with NF‐κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that NF-κB signaling pathway is one of the most important pathways that are activated in macrophages under the pathogen challenge. [34][35][36][37][38] Thus, we aimed to study whether the anti-inflammatory ability of curcumin is associated with NF-κB signaling pathway. By examining the protein expression levels via Western Blotting, we found that IAV infection leads to the decrease in IκBα and cytosolic p65, while enhanced the levels of p-IκBα and nuclear p65.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response activates macrophages and pro‐inflammatory mediators, and cytokines are expressed, such as inducible nitric oxide synthase (iNOS), cyclooxygenase (COX)‐2, interleukin (IL)‐1β, IL‐2, IL‐6, and interferon‐gamma inducible protein 10 kDa (IP‐10). Their overproduction of these molecules is a common marker of the inflammatory response, resulting in various adverse effects (Park et al, ; Yao et al, ). Inhibiting the expression in these inflammatory mediators is important to verify the anti‐inflammatory activity of a natural substance.…”
Section: Resultsmentioning
confidence: 99%
“…Pro‐inflammatory mediators and cytokines were expressed in LPS‐stimulated cells after the transcription factors are translocated to the nucleus. Inhibiting translocation into the nucleus is an important mechanism to regulate inflammation (Kim, Han, Kil, Seo, & Jin, ; Park et al, ; Takeda & Akira, ). To conform for inhibits of solvent fractions, cells were pretreated with the highest concentration of solvent fractions (100 μg/ml) for 2 hr and LPS‐induced inflammatory for 1.5 hr.…”
Section: Resultsmentioning
confidence: 99%
“…Factor-kB and Mitogen-Activated Protein Kinase Pathways Activation in RAW 264.7 Cells It is well-known that NF-kB is an important signaling molecule in the development of inflammatory diseases. In its inactive form, NF-kB exists in the cytoplasm and binds to its inhibitor IkB (Park et al, 2017). Upon activation by LPS, IkB is phosphorylated by IKKa/b, leading to its degradation and NF-kB activation (Qi et al, 2012).…”
Section: Gaudichaudione H Inhibited Nuclearmentioning
confidence: 99%